Adoption and impact of hybrid rice in India: Evidence from a large-scale field survey - Negi, Digvijay S.; Kumar, Anjani; Tripathi, Gaurav; Birthal, Pratap Singh (International Food Policy Research Institute, 2020)
India’s rice production has come under pressure from a number of biotic and abiotic stresses, resulting in a significant deceleration in its productivity growth in recent years. Hybrid rice technology is considered a sustainable option for boosting productivity growth. The adoption rate of hybrid rice technology, however, has remained sluggish. This paper, using data from a large-scale, nationally representative survey of farm households, identifies causes of low adoption of hybrid rice technology and subsequently assesses the impact of low adoption on crop yield. Our findings demonstrate that in India, hybrid rice is often grown on relatively poor soils, resulting in greater costs for irrigation as well as for other inputs, such as fertilizers, essential for growth. Although hybrid rice technology appears to be scale neutral, farmers’ poor access to information on its biochemical traits and agronomic practices, as well as poor access to financial resources, hampers scaling up its adoption. More important, our findings reveal that the relative yield advantage of hybrids over open-pollinated modern varieties is not large enough to incentivize rapid adoption of hybrid rice technology.